2005
DOI: 10.1061/(asce)0733-9429(2005)131:7(596)
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Domain Analysis for Detecting Pipeline Leaks

Abstract: This paper introduces leak detection methods that involve the injection of a continuous fluid transient into the pipeline, creating a time-invariant system that is analyzed in the frequency domain. This method of analysis moves away from the conventional time-domain approach of fluid transients into an area where information concerning the leak is extracted from the frequency behavior of the pipeline system. Two methods of leak detection using the frequency response of the pipeline are proposed, along with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(71 citation statements)
references
References 29 publications
1
69
0
Order By: Relevance
“…Frequency domain diagnosis has been used to detect water pipeline leaks by analyzing pressure responses to steady-oscillatory flows, during which process oscillatory flows are induced into a problematic pipeline section by opening/closing an upstream valve periodically. The power spectra of such fluid transients are affected by pipeline anomalies (e.g., leaks and blockages), thus giving clues that can be used for locating such anomalies [Ferrante and Brunone, 2003;Lee et al, 2005;Mpesha et al, 2001]. Unlike the time domain diagnosis, frequency domain diagnosis is less prone to interference by noise and has long been used as an alternative analysis tool in reservoir characterization (see section 1.2).…”
Section: Introductionmentioning
confidence: 99%
“…Frequency domain diagnosis has been used to detect water pipeline leaks by analyzing pressure responses to steady-oscillatory flows, during which process oscillatory flows are induced into a problematic pipeline section by opening/closing an upstream valve periodically. The power spectra of such fluid transients are affected by pipeline anomalies (e.g., leaks and blockages), thus giving clues that can be used for locating such anomalies [Ferrante and Brunone, 2003;Lee et al, 2005;Mpesha et al, 2001]. Unlike the time domain diagnosis, frequency domain diagnosis is less prone to interference by noise and has long been used as an alternative analysis tool in reservoir characterization (see section 1.2).…”
Section: Introductionmentioning
confidence: 99%
“…1). Details concerning the extraction of the FRD can be found in Lee et al (2004bLee et al ( , 2005. The FRD of a pipeline system contains a series of regular harmonic peaks, spaced according to the fundamental frequency of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al ͑2005͒ has shown that this is the optimum system configuration and will lead to the maximum signal to noise ratio in the measured transient signal. In cases where this configuration cannot be met, a similar oscillation pattern will still be evident in the FRD, although the equation describing this pattern will deviate from Eq.…”
Section: Challenges In Real Systemsmentioning
confidence: 93%